2013
DOI: 10.1007/s12011-013-9646-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Calcium Level, Blood Lipids, and Blood Pressure in Hypertensive and Normotensive Subjects who Come from a Normal University in East of China

Abstract: Previous studies revealed that low calcium intake is related to high prevalence of cardiovascular diseases such as hypertension. However, the relationship between serum calcium and blood pressure was unclear. The prevalence of hypertension is high in China. Thus, the aim of this study was to evaluate the serum calcium level between hypertensive and normotensive groups and to investigate the correlation between serum calcium, blood pressure, and blood lipid parameters. A total of 1,135 adult subjects participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
3
18
4
1
Order By: Relevance
“…On the one hand, the elevation of serum calcium appears to function as a connecting link among various metabolic disorders. Ours and previous studies [ 33 , 36 , 37 , 41 43 ] have demonstrated that serum calcium level was positively and linearly associated with glucolipid metabolic parameters including FPG, HOMA-IR, uric acid, TG, TC and LDL-C. Given that various metabolic abnormalities, such as diabetes [ 3 , 5 ], obesity [ 3 , 5 ], hyperuricemia [ 40 ], insulin resistance [ 21 , 38 , 39 ], and metabolic syndrome [ 21 , 39 , 44 ] have been reported in association with abnormal left ventricular diastolic function, which is the fundamental physiopathologic mechanism responsible for the development of HFpEF [ 45 ], the increased serum calcium level may correlate with HFpEF prevalence through metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 72%
“…On the one hand, the elevation of serum calcium appears to function as a connecting link among various metabolic disorders. Ours and previous studies [ 33 , 36 , 37 , 41 43 ] have demonstrated that serum calcium level was positively and linearly associated with glucolipid metabolic parameters including FPG, HOMA-IR, uric acid, TG, TC and LDL-C. Given that various metabolic abnormalities, such as diabetes [ 3 , 5 ], obesity [ 3 , 5 ], hyperuricemia [ 40 ], insulin resistance [ 21 , 38 , 39 ], and metabolic syndrome [ 21 , 39 , 44 ] have been reported in association with abnormal left ventricular diastolic function, which is the fundamental physiopathologic mechanism responsible for the development of HFpEF [ 45 ], the increased serum calcium level may correlate with HFpEF prevalence through metabolic abnormalities.…”
Section: Discussionsupporting
confidence: 72%
“…Findings in this recent study is contradictive with a previous study conducted by Yao, Y et al, in China that reported there is a significant positive correlation between calcium serum level and systolic blood pressure in hypertensive patients compared to normotensive people, also calcium serum levels in hypertensive patients tend to be low compared to normotensive people [27]. This is consistent with literature theory that explained how the mechanism of low calcium intake could regulate blood pressure by increasing intracellular calcium in vascular smooth cells resulting in vasoconstriction, also increase in vascular volume through Renin-Angiotensin-Aldosterone System (RAAS).…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have shown higher concentrations of calcium to be associated with increased risk of hypertension, 6,7 whereas some have reported a protective effect, 8,9 and others have reported null associations. 10,11 In addition, these studies have relied on total or albumin-corrected estimates of serum calcium, which only approximate the levels of biologically active serum calcium (iCa).…”
mentioning
confidence: 99%